PENGARUH MERCHANDISING, PROMOSI DAN ATMOSFIR TOKO TERHADAP IMPULSE BUYING - Sari, Dewa Ayu Taman; Suryani, Alit (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Retail business is growing so rapidly . Retailer sales turnover obtained can be sourced from impulse buying . Impulse buying can occur due to the influence of stimulus spending in the form of external stimuli . This study focuses on the influence of external stimuli such as merchandising , promotions and store atmosphere against impulse buying customers Tiara Dewata Supermarket Denpasar . Purposive sampling was used for the sampling technique that takes 114 respondents and multiple linear regression analysis as a technique of data analysis . This study found that merchandising , promotions and store atmosphere simultaneously significant and partial significant positive effect on impulse buying . Management is advised to continue to maintain and enhance the activities of merchandising , promotions and store atmosphere that has been done in order to survive in the fierce competition . Key words : merchandising , promotion , store atmosphere and impulse buying